SAT0667 Implementation and role of modern musculoskeletal imaging in rheumatological practice in europe. (12th June 2018) - Mandl, P.; Ciechomska, A.; Baraliakos, X.; Conaghan, P.G.; D'Agostino, M.-A.; Iagnocco, A.; van der Laken, C.J.; Ostergaard, M.; Terslev, L.; Naredo, E.
Abstract : Background: Modern non-X-ray imaging methods are increasingly utilised by rheumatologists though the uptake and use of these techniques has developed very differently across Europe and there is limited data on their present impact in rheumatology for individual countries. Objectives: To document the current implementation, role and training in modern musculoskeletal imaging techniques: musculoskeletal ultrasound (MSUS), magnetic resonance imaging (MRI), computed tomography (CT), and positron emission tomography (PET) among rheumatologists in the member countries of the European League Against Rheumatism (EULAR). Methods: A EULAR Taskforce comprised of 9 rheumatologist experts in imaging developed English-language questionnaires for each imaging modality (CT, MRI, MSUS, PET) which were sent out to: national rheumatology societies of EULAR, national societies of the European Federation of Societies for Ultrasound in Medicine and Biology, the European Society for Magnetic Resonance Ultrasound in Medicine and Biology, as well as identified experts in the given modalities involved in research and/or training. The surveys were distributed via an online survey tool (Surveymonkey). Simple descriptive and summary statistics were calculated from the responses. Results: A total of 205 out of 395 experts replied to the surveys. More than 90% of MSUS experts had an MSUS unit in their department. The majority of responders reported having easy access to MRI, CT or PET (56%, 78% and 50% respectively). Suspicion of rheumatoid arthritis and peripheral spondyloarthrity were the main clinical indications for performing MSUS for diagnostic purposes. Suspicion of sacroiliitis and degenerative spine disease were the most common indications to perform MRI or CT for diagnostic purposes, while PET was mainly performed to diagnose large vessel vasculitis and investigation of fever of unknown origin. When asked about the percentage of rheumatologists performing MSUS in their country 37% of experts reported less than 20%, 33% reported values between 20%–40% and 24% reported more than 40% (6%: unknown). The overwhelming majority (99%) of experts were certified in MSUS, while only 22% and 26% of experts in MRI and CT were certified in their techniques. Seventy-seven percent of responders reported that their national rheumatology societies organise MSUS courses, while courses in MRI or CT organised by the national rheumatology societies were less commonly reported (38% and 16% respectively). Conclusions: Rheumatologists in Europe utilise modern imaging techniques, however access among the techniques and training offered is varied. Disclosure of Interest: None declared